Night of the living dummy eaudiobook - Stine, R. L. (Goosebumps, 2017)
Discover the original bone-chilling adventures that made Goosebumps one of the bestselling children's book series of all time! Lindy names the ventriloquist's dummy she finds Slappy. Slappy is kind of ugly, but he's a lot of fun. Lindy's having a great time learning to make Slappy move and talk. But Kris is jealous of all the attention her sister is getting. It's no fair. Why does Lindy always have all the luck?Kris decides to get a dummy of her own. She'll show Kris. Then weird things begin to happen. Nasty things. Evil things. No way a dummy can be causing all the trouble. Or is there?Now with all-new bonus material revealing Slappy's secrets and more.